Copolymeric polycarbonate resin composition, molded article, and method for producing copolymeric polycarbonate resin
A co-polymerized polycarbonate resin with polyol siloxane and aliphatic dihydroxy compounds addresses the limitations of conventional polycarbonate resins by enhancing chemical and weather resistance while maintaining transparency, suitable for diverse applications.
Patent Information
- Application Number
- JP2021052930
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-03-26
AI Technical Summary
Conventional polycarbonate resins exhibit inadequate chemical resistance, weather resistance, and transparency, particularly when using bisphenol A as a raw material, which deteriorates due to UV absorption from the benzene ring structure.
A co-polymerized polycarbonate resin is developed with structural units derived from polyol siloxane and aliphatic dihydroxy compounds, such as isosorbide, to enhance chemical and weather resistance, featuring a spiro ring structure for improved compatibility and transparency.
The co-polymerized polycarbonate resin achieves high chemical resistance, weather resistance, and transparency, making it suitable for various applications including automotive parts, electronic components, and outdoor materials.
Smart Images

Figure 0007622506000022 
Figure 0007622506000001 
Figure 0007622506000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer polycarbonate resin, and more particularly to a copolymer polycarbonate resin having chemical resistance, This relates to polycarbonate with excellent weather resistance. [Background technology]
[0002] Polycarbonate resins are generally made from bisphenols as monomer components, and are highly transparent, durable, and Taking advantage of its superior thermal resistance and mechanical strength, it is used in electrical and electronic parts, automotive parts, medical parts, construction In the fields of materials, films, sheets, bottles, optical recording media, lenses, etc., In recent years, these applications have seen a rapid growth in the number of applications. However, there is a demand for further improvements in the performance of processed products using bisphenol A as a raw material. Conventional polycarbonate resins, which are used for this purpose, do not have the chemical resistance or durability required for these requirements. Therefore, the development of polycarbonate resin with improved chemical resistance and weather resistance has been attempted. There has been a demand for such a system, and several proposals have been made.
[0003] For example, the chemical resistance of polycarbonate made from bisphenols as raw material monomers As a means for improving the above, a method for copolymerizing a specific amount of a specific polyorganosiloxane is disclosed. It has been reported (Patent Document 1). The bisphenol compounds used in conventional polycarbonate resins have a benzene ring structure. This leads to a large ultraviolet absorption, which deteriorates the light resistance of polycarbonate resin. This is a contributing factor.
[0004] Therefore, aliphatic dihydroxy compounds and alicyclic dihydroxy compounds that do not have a benzene ring structure in the molecular skeleton are Hydroxy compounds, cyclic dihydroxy compounds with ether bonds in the molecule such as isosorbide Polycarbonate resins using raw material monomers such as the compound have been developed (Patent Document For example, polyolefins made from isosorbide obtained from biomass resources are It has been disclosed that recarbonate resins have high weather resistance (Patent Document 6). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 029841 Brochure [Patent Document 2] International Publication No. 2004 / 111106 Brochure [Patent Document 3] International Publication No. 2007 / 063823 Brochure [Patent Document 4] International Publication No. 2008 / 108492 Brochure [Patent Document 5] JP 2011-241277 A [Patent Document 6] JP 2013-209585 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, conventional methods have not been able to obtain polycarbonate resins with excellent chemical resistance and weather resistance. It was not possible to do so. Aromatic-polyorganosiloxane copolymerized polycarbonate as described in Patent Document 1 There is no description of the weather resistance of nate resin, and the inventors' investigation revealed that it has poor weather resistance. It was found that:
[0007] In addition, the isosorbide described in Patent Document 4, which does not have a benzene ring structure in its molecular skeleton, is used as a raw material. The monomer used is a polyorganosiloxane-modified polycarbonate resin, Isosorbide, as described in Reference 5, was used as a raw monomer and copolymerized with polyorganosiloxane. There is no description of the chemical resistance of polycarbonate resin. In addition, all polycarbonate resins had poor transparency. It was something like that.
[0008] Under such circumstances, an object of the present invention is to provide a polycarbonate resin having excellent chemical resistance and weather resistance. The purpose of this invention is to provide [Means for solving the problem]
[0009] In order to solve the above problems, the present inventors have conducted extensive research and have discovered a specific structure of a dihedral junction. The polyorganosiloxane has a structural unit derived from a hydroxy compound and a structural unit derived from a polyorganosiloxane. The copolymer polycarbonate has high chemical resistance, weather resistance, and is surprisingly transparent. The present inventors have found that the composition may also have excellent properties such as excellent moisture absorption resistance and excellent adhesion, and have arrived at the present invention. That is, the gist of the present invention resides in the following [1] to [9]. [1] A polyol having a structural unit (A) represented by the following formula (1) and two or more reactive functional groups: A copolymer polycarbonate resin containing structural units (B) derived from siloxane.
[0010] [ka]
[0011] In the formula (1), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms. Xylene group; R 1 ~R2 has a branched or linear alkyl group having 1 to 20 carbon atoms, or a substituent a cycloalkyl group having 6 to 20 carbon atoms; m is an integer of 0 to 10) [2] The total weight of all structural units and linking groups constituting the resin is taken as 100% by weight. When the content of the structural unit (A) is 40% by weight or more and 90% by weight or less, the content of the structural unit (B) is The copolymer polycarbonate according to [1], wherein the content is 1.0% by weight or more and 20% by weight or less. resin. [3] The ratio of the content of the structural unit (A) to the content of the structural unit (B) is 96 / 4 to 70 / 30; The copolymer polycarbonate resin according to [1] or [2]. [4] The reactive functional groups are each independently a hydroxyl group, a carboxyl group, an amino group, an alkoxy group, acryloyl group, ester group, methacryloyl group, acryloyl group, and cyclic ether group. The copolymer polycarbonate according to any one of [1] to [3], which is one or more selected from the group consisting of Neate resin. [5] The copolymer according to any one of [1] to [4], wherein the structural unit (B) is represented by the following formula (2): Synthetic polycarbonate resin.
[0012] [ka]
[0013] (In formula (2), n is 5 to 30. R 3 ~R 6 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. X and X' each independently represent an oxygen atom, or an organic residue having -C(=O)-, an ether structure, an amine structure, an aromatic structure, or an aliphatic structure. n represents the average number of repetitions of the polyorganosiloxane portion. [6] A copolymeric polycarbonate resin according to any one of [1] to [5], containing structural units (C) derived from one or more compounds selected from the group consisting of aliphatic dihydroxy compounds, alicyclic dihydroxy compounds, oxyalkylene glycols, and dihydroxy compounds containing an acetal ring in a total amount of 5% by weight or more and 30% by weight or less, when the total weight of all structural units and linking groups constituting the resin is taken as 100% by weight. [7] The copolymer polycarbonate resin according to any one of [1] to [6], wherein the polycarbonate resin has a water absorption rate of 1.1% or less. [8] The copolymer polycarbonate resin according to any one of [1] to [7], wherein the copolymer polycarbonate resin has a glass transition temperature of 50° C. or higher and 160° C. or lower. [9] A molded article comprising the copolymer polycarbonate resin according to any one of [1] to [8].
[10] A dihydroxy compound including a dihydroxy compound represented by the following formula (3) and a compound having two or more reactive functional groups: Rupo A method for producing a copolymeric polycarbonate resin, comprising: mixing a triorganosiloxane to obtain a raw material solution; and subjecting the raw material solution to a polycondensation reaction with a carbonic acid diester and a polymerization catalyst.
[0014] [ka]
[0015] In the formula (3), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms. Xylene group; R 1 ~R 2 has a branched or linear alkyl group having 1 to 20 carbon atoms, or a substituent a cycloalkyl group having 6 to 20 carbon atoms; m is an integer of 0 to 10)
[0016] [Reasons why the present invention is effective] The reason why the present invention is effective is not yet clear, but is presumed to be as follows. Polyorganosiloxanes have a low polarity due to their siloxane structure, and are widely used in various dihydroxylation reactions. Therefore, when polycarbonate resin is polymerized by melt polymerization, When the siloxane and dihydroxy compounds were melted, the reaction solution separated into two layers and The reaction is homogeneous. If the reaction solution is inhomogeneous, the reaction of polyorganosiloxane alone will not occur. The dispersion of the structural unit domains derived from the polyorganosiloxane in the polymer becomes poor. As a result, the chemical resistance of the resulting polymer deteriorates. This is thought to result in a decrease in transparency.
[0017] As a result of the investigations conducted by the present inventors, it was surprisingly found that the spiro ring structure of a cyclic acetal It was found that dihydroxy compounds having the above structure have high affinity with polyorganosiloxane. In other words, polyorganosiloxane and a dihydroxy compound having a spiro ring structure are melt-polymerized. At times, the reaction solution becomes homogeneous, so the reaction of polyorganosiloxane alone is reduced and the polymer The dispersion of the structural unit domains derived from the polyorganosiloxane in the polymer is improved, and at the same time, the dots are As a result, the resulting polymer exhibits high chemical resistance and, in some aspects, On the other hand, the transparency is improved when the dihydroxy compound has a heterocyclic structure. In the case of a combination of only isosorbide, which is a compound of the formula I, and polyorganosiloxane, the isosorbide is in the ring. Since it does not have a spiro ring structure of acetal, it is difficult to obtain a good reaction between isosorbide and polyorganosiloxane. The affinity of the structural unit domain derived from the polyorganosiloxane in the polymer is relatively poor. This results in poor dispersion of the ink and poor chemical resistance of the resulting polymer. Effect of the Invention
[0018] The polycarbonate copolymer of the present invention has high chemical resistance and weather resistance. Some of the clear embodiments of the present invention have excellent transparency and moisture absorption resistance in addition to high chemical resistance and weather resistance. Since the polycarbonate copolymer has such excellent properties, it is suitable for use in automobile interiors and exteriors. Used in a wide range of fields, including components, electrical components, electronic and electrical materials, outdoor building components, and cosmetic containers. It can be used. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a cross-sectional view of a 1 / 4 elliptical jig used in chemical resistance tests. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below, but the present invention is not limited to the following description. The invention can be modified and implemented in any manner without departing from the spirit and scope of the invention. In this specification, when "~" is used to express a numerical value or a physical property value, It will be used including the values before and after it. In this specification, the term "repeating structural unit" refers to a structure in which the same structure appears repeatedly in a resin. It means a structural unit that constitutes the resin by linking each other. For example, in the case of polycarbonate resin, the carbonyl group is also called the repeating structural unit. In addition, the term "structural unit" refers to a partial structure that constitutes a resin, and is a repeating structural unit. For example, a specific partial structure sandwiched between adjacent linking groups in a resin. The polymerizable reactive group present in the partial structure or the terminal portion of the polymer and the linking group adjacent to the polymerizable reactive group More specifically, in the case of polycarbonate resin, A carbonyl group is a linking group, and a partial structure sandwiched between adjacent carbonyl groups is called a structural unit. In this specification, the weight ratio of each structural unit in the polycarbonate resin is The total weight of all structural units and linking groups is calculated as 100% by weight.
[0021] [Structure and raw materials of copolymer polycarbonate resin] The copolymeric polycarbonate resin according to the first aspect of the present invention has a structural unit represented by the following formula (1): A structural unit (B) derived from a polyorganosiloxane having two or more reactive functional groups and a ) is a copolymer polycarbonate resin containing.
[0022] [ka]
[0023] In the formula (1), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms. Xylene group; R 1 ~R 2 has a branched or linear alkyl group having 1 to 20 carbon atoms, or a substituent a cycloalkyl group having 6 to 20 carbon atoms; m is an integer of 0 to 10) Examples of the alkylene group having 1 to 20 carbon atoms include a methylene group, an ethylene group, and an n-propylene group. , isopropylene group, n-butylene group, 1-methylethylene group, 1-ethylethylene group, Examples include an n-pentylene group and an n-hexalene group.
[0024] Examples of the cycloalkylene group having 6 to 20 carbon atoms include a cyclohexalene group, a cycloheptalene group, and Examples of the substituent include aryl groups. Examples of the branched or linear alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, an n-propyl group, Examples include a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. can be.
[0025] Examples of the cycloalkyl group having 6 to 20 carbon atoms which may have a substituent include cyclohexa Examples of the aryl group include a cyclohexane group and a cycloheptane group. Among these, W is preferably an alkylene group having 1 to 20 carbon atoms, It is more preferable that the alkylene group has 1 to 10 carbon atoms, and particularly preferable that the alkylene group has 1 to 5 carbon atoms. R is preferably an ethylene group. 1 and R 2 are each independently the number of carbon atoms A branched or linear alkyl group having 1 to 20 carbon atoms is preferred, and a branched or linear alkyl group having 1 to 10 carbon atoms is preferred. A straight-chain alkyl group is more preferable, and a branched or straight-chain alkyl group having 1 to 5 carbon atoms is more preferable. is particularly preferred, and a methyl group is most preferred. m is an integer of 0 to 10. In this formula, m is preferably an integer of 0 to 6, and more preferably an integer of 0 to 4.
[0026] The structural unit (A) represented by the above formula (1) is a structure represented by the following formula (Y): In this case, the reactivity during polymerization and the ease of availability are excellent.
[0027] [ka]
[0028] The structural unit (A) represented by the above formula (1) is derived from a diol having a spiro ring structure. As a diol compound having such a spiro ring structure, 3,9-bis(2 -hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2,4,8,10-tetrahydrofuran Oxaspiro(5.5)undecane, 3,9-bis(2-hydroxy-1,1-diethyl Ethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, 3,9-bis (2-Hydroxy-1,1-dipropylethyl)-2,4,8,10-tetraoxaspirillum (5.5) alicyclic diol compounds such as undecane. Particularly preferred are the following compounds: 3,9-bis(2-hydroxy-1,1-dimethylethyl)-2, 4,8,10-Tetraoxaspiro(5.5)undecane (also called spiroglycol) In some cases, the following is used:
[0029] [ka]
[0030] The copolymeric polycarbonate resin of the present invention is a copolymer of the above-mentioned structural units and linking groups. When the total weight of the above is taken as 100% by weight, the structural unit (A) represented by the above formula (1) is 4 It is preferable that the content is 0% by weight or more, more preferably 45% by weight or more, and more preferably 50% by weight or more. More preferably, the content is 55% by mass or more, even more preferably, 60% by mass or more. It is particularly preferable that the content is 70% by weight or more, and most preferable that the content is 90% by weight or less. It is preferable that the content is 85% by weight or less, and more preferable that the content is 80% by weight or less. When the structural unit (A) is equal to or more than the lower limit, the heat resistance of the polycarbonate resin is improved. In addition, when the structural unit (A) is equal to or less than the above lower limit, the polycarbonate resin is preferred because it does not crystallize during polymerization and polymerization is easy.
[0031] The copolymeric polycarbonate resin of the present invention is a copolymer of the above-mentioned structural units and linking groups. When the total weight of the polyorgano group is taken as 100% by weight, It is preferable that the structural unit (B) derived from siloxane is contained in an amount of 1.0% by weight or more, and 2. It is more preferable that the content is 0% by weight or more, and further preferably that the content is 3.0% by weight or more. It is preferable that the content is 4.0% by weight or more, and it is particularly preferable that the content is 20% by weight or less. It is preferable that the content is 15% by weight or less, more preferably 10% by weight or less. In the copolymeric polycarbonate resin of the present invention, the structural unit (B) is mainly Since the structural unit (B) has the function of improving chemical resistance, the content of the structural unit (B) is equal to or higher than the above lower limit. In addition, when the structural unit (B) is equal to or less than the upper limit, sufficient chemical resistance can be obtained. In addition, the transparency of the polycarbonate resin is improved. This improves reactivity and makes it easier to proceed with the polymerization reaction until a sufficient molecular weight is achieved.
[0032] The copolymer polycarbonate resin of the present invention contains the structural unit (A) and the structural unit (B). The ratio of the amounts is preferably 96 / 4 to 70 / 30 by weight. When the ratio of 100 to 150 is included, sufficient chemical resistance can be obtained. The transparency of the resin is improved. Furthermore, the reactivity during polymerization of the polycarbonate resin is improved, From the same viewpoint, the structural unit (A) and the structural unit (B) are preferably used as the structural unit (C). The ratio of the contents of the units (B) is more preferably 96 / 4 to 80 / 20, and even more preferably Mostly between 95 / 5 and 85 / 15.
[0033] (Polyorganosiloxane) Organopolysiloxane is a polymer with siloxane bonds as the main chain. Specifically, it refers to a polysiloxane skeleton and a polysiloxane It is a polymer in which a substituent (i.e., an organic group) is bonded to the siloxane bond of the skeleton. The organopolysiloxanes used are polymerized as structural units of copolymerized polycarbonate resins. When incorporated through a reaction, it has two or more reactive functional groups. By having two or more reactive functional groups, the copolymer polycarbonate resin polymer chain can be A structural unit derived from polyorganosiloxane can be introduced into the polyol. When the organosiloxane has only one reactive functional group, the reaction is carried out in a manner similar to that of a polyorganosiloxane. The resulting structural units are introduced only at the ends of the polymer chains, Recarbonate resins do not provide sufficient chemical resistance.
[0034] The reactive functional group is a carbon atom, a hydrogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, It is composed of one or more atoms selected from silicon atoms and halogens, and is present in the air or In a solvent, at a temperature range that is normally used (e.g., 100 to 300°C), it is possible to react with other functional groups. A group whose chemical structure can change upon contact or heating. The functional group is, for example, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, a silicon atom, a halogen atom, or carbon-carbon multiple bonds (i.e., unsaturated bonds such as double bonds, triple bonds, etc.) It is a functional group.
[0035] The reactive functional group is not particularly limited, but from the viewpoint of high reactivity, a multi-carbon functional group is preferred. The functional group is preferably a functional group having a double bond and / or a functional group containing an oxygen atom. Nyl group, ester group, methacryloyl group, acryloyl group, cyclic ether group, alcohol a hydroxyl group, a phenolic hydroxyl group, a silanol group, and a carboxyl group. From the viewpoint of higher reactivity, it is more preferable that the functional group is at least one of The reactive functional group is more preferably an alcoholic hydroxyl group or a silanol group. An alcoholic hydroxyl group is particularly preferred.
[0036] The structural unit (B) derived from a polyorganosiloxane having two or more reactive functional groups is preferably It is preferably represented by the following formula (2).
[0037] [ka]
[0038] (In formula (2), n is 5 to 30. R 3 ~R 6 are each independently a hydrogen atom, a halo a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a group having 6 to 12 carbon atoms X and X' are residues of reactive functional groups of polyorganosiloxane. Specifically, each independently represents an oxygen atom, -C(=O)-, an ether structure, n represents an organic residue having an amine structure, an aromatic structure or an aliphatic structure. (The average number of repeats of the siloxane part is shown.)
[0039] As described above, n represents the average repeat number of the polyorganosiloxane. The number of bonds is preferably 5 or more, more preferably 6 or more, and even more preferably 7 or more. Preferably, the number is 25 or less, more preferably 20 or less, and particularly preferably 15 or less. When the average number of repetitions is equal to or greater than the lower limit, sufficient chemical resistance can be obtained. When the average repeat number is equal to or less than the upper limit, the transparency is significantly improved. When the average number of siloxane repeats is relatively small, the polyorgano groups in the polymer chain The structural units derived from siloxane are appropriately dispersed to eliminate localized non-uniformity in the refractive index. This is presumably because the clouding caused by the precipitation is suppressed.
[0040] R 3 ~R 6 each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms, It is an alkoxy group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms. Examples of halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. . Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, and an n-butyl group. , isobutyl group, and the like.
[0041] Examples of the alkoxy group having 1 to 6 carbon atoms include a methoxy group and an ethoxy group. Examples of the aryl group having 6 to 12 carbon atoms include a phenyl group and a naphthyl group. R 3 ~R 6 are each independently preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms, R is preferably a phenyl group. 3 ~R 6 are different but the same However, from the viewpoint of excellent effect of improving chemical resistance, R 3 ~R 6 But eventually are preferably the same, and R 3 ~R 6are both methyl groups or both phenyl groups More preferably, R 3 ~R 6 It is most preferable that each of the groups is a methyl group.
[0042] X and X' are each independently a silanol residue or an alcoholic hydroxyl group residue. From the viewpoint of the reactivity of the polyorganosiloxane, a residue of an alcoholic hydroxyl group is preferable. More preferably, it is a carbinol residue. X and X' are each independently a structure represented by the following formula (W): In this case, the reactivity and transparency are excellent.
[0043] [ka]
[0044] (In formula (W), * represents a bonding site between X or X' and the adjacent silicon atom in formula (2). * represents the bonding site on the opposite side to the silicon atom in formula (2). The structure represented by the above formula (2) is particularly preferably a structure represented by the following formula (Z): In this case, the reactivity and transparency are excellent.
[0045] [ka]
[0046] (Other structural units) The copolymerized polymer carbonate resin of the present invention is a copolymer having a structure unit (A) represented by the above formula (1) and In addition to the structural unit (B) derived from polyorganosiloxane having two or more cyclic functional groups, aromatic dihydroxy compounds, alicyclic dihydroxy compounds, oxyalkylene glycols, and Derived from one or more compounds selected from the group consisting of dihydroxy compounds having a heterocyclic structure The copolymer may contain a structural unit (hereinafter, sometimes referred to as structural unit (C)). Among these, aliphatic dihydroxy compounds and alicyclic dihydroxy compounds are preferred from the viewpoint of superior mechanical properties. A compound selected from the group consisting of a hydroxy compound and a dihydroxy compound having a heterocyclic structure. It is preferred to have structural units derived from one or more compounds.
[0047] Examples of the aliphatic dihydroxy compound include ethylene glycol and 1,2-propane Diol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol 1,4-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-Pentanediol, 1,5-Pentanediol, 1,2-Hexanediol, 1 ,3-Hexanediol, 1,4-Hexanediol, 1,5-Hexanediol, 1, 6-Hexanediol, 1,7-Heptanediol, 1,8-Octanediol, 1,9 -nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,1 Linear aliphatic dihydroxy compounds such as 2-dodecanediol, neopentyl glycol, 2 -Ethyl-1,6-hexanediol, 2,2,4-trimethyl-1,6-hexanediol Branched chain aliphatic diglycerides such as hydrogenated dilinoleyl glycol, hydrogenated dioleyl glycol, etc. Examples of hydroxy compounds include ethylene glycol, 1,3 -Propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol Xanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nona 1,10-Decanediol, 1,11-Undecanediol, 1,12-Decanediol Linear aliphatic dihydroxy compounds such as decanediol are easy to obtain and handle. This is preferable from the viewpoint of compactness.
[0048] Examples of the alicyclic dihydroxy compound include the following dihydroxy compounds: 1,2-Cyclohexanedimethanol, 1,3-Cyclohexanedimethanol, 1,4 -Cyclohexanedimethanol, Tricyclodecanedimethanol, Pentacyclopentadecane Candimethanol, 2,6-Decalindimethanol, 1,5-Decalindimethanol, 2 ,3-Decalin dimethanol, 2,3-Norbornane dimethanol, 2,5-Norborna Terpene compounds such as 1,3-adamantanedimethanol, limonene, etc. Dihydroxy compounds derived from alicyclic hydrocarbons are exemplified by primary alcohols of alicyclic hydrocarbons. Dihydroxy compounds; 1,2-cyclohexanediol, 1,4-cyclohexanediol 1,3-Adamantanediol, Hydrogenated Bisphenol A, 2,2,4,4-Tetramethylenediol Alicyclic hydrocarbon secondary alcohols, such as ethyl-1,3-cyclobutanediol, etc. or a dihydroxy compound which is a tertiary alcohol.
[0049] Examples of oxyalkylene glycols include diethylene glycol, triethylene glycol, ethylene glycol, tetraethylene glycol, polyethylene glycol, polypropylene glycol Licor, polytetramethylene glycol, etc. can be used. The dihydroxy compound having a heterocyclic structure is a dihydroxy compound represented by the following formula (4): and dihydroxy compounds containing an acetal ring other than the structure represented by the above formula (1). Things are given as examples.
[0050] [ka]
[0051] The dihydroxy compound represented by the above formula (4) is a stereoisomeric compound. These dihydroxy compounds (4 ), which is an abundant and readily available resource and is produced from various starches. Isosorbide, which is obtained by dehydrating and condensing sorbitol, is easy to obtain and produce, and is easy to mold. These dihydroxy compounds (4) can be used alone or in combination. It is also possible to use two or more of them in combination.
[0052] As a dihydroxy compound containing an acetal ring other than the structure represented by the above formula (1), For example, dioxane glycol represented by the following formula (5) can be used.
[0053] [ka]
[0054] In addition to the above, the dihydroxy compound having a heterocyclic structure may be represented by the following formula (4): The dihydroxy compound containing the dihydroxy compound and the carbonic acid diester are subjected to a polycondensation reaction. Examples of the polycarbonate diol include polycarbonate diols. The above-mentioned aliphatic dihydroxy compounds, alicyclic dihydroxy compounds, oxyalkylene One or more selected from the group consisting of ricor, and dihydroxy compounds having a heterocyclic structure The compounds include 1,6-hexanediol, 2,2,4,4-tetramethyl-1,3 -Cyclobutanediol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol Structural units derived from ethanol, dioxane glycol, isosorbide, and isosorbide It is particularly preferable to use polycarbonate diols containing these monomers. Polycarbonate resins containing structural units with excellent balance of optical properties, heat resistance, mechanical properties, etc. It's even better.
[0055] The copolymeric polycarbonate resin of the present invention is a copolymer of aliphatic dihydroxy compounds, alicyclic dihydroxy compounds, Dihydroxylated oxy compounds, oxyalkylene glycols, and acetal ring-containing dihydroxylated In the case where the structural unit (C) is derived from one or more compounds selected from the group consisting of is the weight percent of the total weight of all structural units and linking groups constituting the resin. The structural unit (C) is preferably contained in an amount of 5% by weight or more, and more preferably 6% by weight or more. It is more preferable that the content is 7% by weight or more, and even more preferable that the content is 30% by weight or less. It is preferable that the content is 25% by weight or less, and more preferable that the content is 20% by weight or less. When the structural unit (C) is within the above range, the copolymer polycarbonate It is possible to balance other physical properties such as heat resistance and melt processability without significantly impairing the excellent properties of the acrylate resin. The speed can be adjusted.
[0056] The copolymer carbonate resin of the present invention is preferably a copolymer of the above-mentioned aliphatic dihydroxy compound, Cyclic dihydroxy compounds, oxyalkylene glycols, and dihydroxy compounds having heterocyclic structures In addition to the structural units derived from the aromatic dihydroxy compound, the structural units may also include structural units derived from the aromatic dihydroxy compound. . Examples of aromatic dihydroxy compounds include 2,2-bis(4-hydroxyphenyl ) Propane [= Bisphenol A], 2,2-bis(4-hydroxy-3,5-dimethyl phenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl) Propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis bis(4-hydroxyphenyl)pentane, 2,4'-dihydroxy-diphenylmethane, Bis(4-hydroxyphenyl)methane, Bis(4-hydroxy-5-nitrophenyl) Methane, 1,1-bis(4-hydroxyphenyl)ethane, 3,3-bis(4-hydroxyphenyl)ethane 1,1-bis(4-hydroxyphenyl)cyclohexane, (4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenyl sulfone, Bis(4-hydroxyphenyl)sulfide, 4,4'-dihydroxydiphenyl ether 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether, 9,9-biphenyl Fluorene, 9,9-bis(4-(2-hydroxyethoxy-2-methyl)phenyl) Bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-2-methyl and aromatic dihydroxy compounds such as phenyl)fluorene.
[0057] The copolymeric polycarbonate resin of the present invention is a copolymer of the above-mentioned structural units and linking groups. When the total weight of the above is taken as 100% by weight, the structural unit derived from an aromatic dihydroxy compound is When the copolymer contains 15% by weight or less, the content is preferably 10% by weight or less, and more preferably 5% by weight or less. It is more preferable that the content of the aromatic bisphenols is 0% by weight or less, and particularly preferable that the content of the aromatic bisphenols is 0% by weight or less. When the structural unit is within the above range, deterioration of weather resistance due to ultraviolet absorption of the benzene ring structure is prevented. It can be suppressed.
[0058] (carbonic acid diester) The linking group of the structural unit contained in the polycarbonate resin of the present invention is represented by the following formula (6): It is introduced by polymerizing a carbonate diester represented by the following formula:
[0059] [ka]
[0060] (In formula (6), R 7 and R 8 each of which may have a substituent and has 1 to 18 carbon atoms an aliphatic hydrocarbon group or an aromatic hydrocarbon group which may have a substituent, R 7 and R 8 may be the same or different.) R 7 and R 8 is preferably a substituted or unsubstituted aromatic hydrocarbon group, The aromatic hydrocarbon group is more preferred. The substituent of the aliphatic hydrocarbon group is preferably an ester. groups, ether groups, amide groups, and halogen atoms. Examples of the alkyl group include a methyl group, an ethyl group, and the like.
[0061] The carbonic acid diester represented by the formula (6) is, for example, diphenyl carbonate ( Hereinafter, this may be abbreviated as DPC.) and substituted diphenyl carbonates such as ditolyl carbonate carbonate, dimethyl carbonate, diethyl carbonate and di-tert-butyl carbonate Examples of the dialkyl carbonate include dialkyl carbonates such as diphenyl carbonate. and substituted diphenyl carbonates, particularly preferably diphenyl carbonate. . Carbonate diesters may contain impurities such as chloride ions, and these impurities may polymerize. If necessary, do not use any additives, as this may inhibit the reaction or deteriorate the color of the resulting resin. It is preferable to use one that has been purified by distillation or the like.
[0062] [Physical properties of copolymer polycarbonate resin] The copolymeric polycarbonate resin of the present invention preferably has the following physical properties: .
[0063] (Total light transmittance) The copolymer polycarbonate resin of the present invention preferably has a total light transmittance of 88% or more. More preferably, 89% or more, even more preferably 90% or more, and even more preferably 91% or more When the total light transmittance is equal to or higher than the lower limit, the material can be suitably used as a transparent material. The total light transmittance of the copolymer polycarbonate resin is measured by the method described in the examples. It is possible.
[0064] (Water absorption rate) The water absorption rate of the copolymeric polycarbonate resin of the present invention is preferably 1.1% or less, more preferably The water absorption rate is preferably 1.05% or less, and more preferably 1.0% or less. It is preferable in terms of moisture absorption resistance and low dimensional change rate. The water content can be measured by the method described below. Water Absorption of Copolymer Polycarbonate Resin can be appropriately adjusted by, for example, changing the type and ratio of structural units constituting the resin. can be done.
[0065] (glass transition temperature) The glass transition temperature of the copolymer polycarbonate resin of the present invention is preferably 40° C. or higher. The glass transition temperature is preferably 5° C. or higher, and more preferably 50° C. or higher. If there is any, there is a risk that copolymer polycarbonate resin or its molded products will adhere or deform at room temperature. In addition, the glass transition temperature of the copolymer polycarbonate resin is preferably 145°C or lower. The glass transition temperature is preferably 135° C. or less, more preferably 125° C. or less. When the content is equal to or less than the upper limit, the flowability during molding is increased, and even molded products with complex shapes can be molded with ease. The polycarbonate resin can easily reach the ends of the mold, making it possible to obtain the desired molded product. In addition, it is possible to prevent the strength of the welds from decreasing. The glass transition temperature of the copolymer polycarbonate can be measured by the method described in the Examples. The glass transition temperature of the ester resin can be changed by, for example, changing the type and ratio of the structural units constituting the resin. This allows for appropriate adjustment.
[0066] (Chemical resistance) The copolymer polycarbonate resin of the present invention is a nonionic surfactant using a 1 / 4 elliptical jig. In a chemical resistance test using a heat-resistant agent, the critical strain is preferably 0.5 or more, and more preferably 0.6 or more. It is more preferable that the ratio is 0.5 or more, and further preferably 0.7 or more. When the critical strain of the carbonate resin is equal to or higher than the lower limit, it is possible to use the resin in applications such as automobile interior and exterior components, electrical components, electronic and electrical components, etc. It can be used for materials, outdoor building materials, and cosmetic containers. The glass transition temperature of the resin can be measured by the method described in the Examples.
[0067] (weather resistance) The copolymer polycarbonate resin of the present invention is irradiated with light at an irradiation intensity of 60 W / m 2100 hours treatment under the conditions In a weather resistance test in which the film is subjected to a weather resistance test, it is preferable that the ΔYI value before and after the test is 1.0 or less, The copolymer polycarbonate resin has a viscosity of 0.6 or less, more preferably 0.2 or less. When ΔYI is equal to or less than the upper limit, the film can be suitably used for outdoor applications such as automobile interior and exterior components and building components. The weather resistance of the copolymer polycarbonate resin can be measured by the method described in the Examples. It can be determined.
[0068] [Method for producing polycarbonate resin of the present invention] The polycarbonate resin of the present invention can be produced by a commonly used polymerization method. For example, solution polymerization or interfacial polymerization using phosgene or carboxylic acid halides, The polymer can be produced by a melt polymerization method in which the reaction is carried out without using a catalyst. As it does not use solvents or highly toxic compounds, it reduces the environmental impact. In addition, it is preferable to produce it by the melt polymerization method, which is excellent in productivity.
[0069] In addition, if a solvent is used in polymerization, the solvent may remain in the resin, and its plasticizing effect may This lowers the glass transition temperature of the resin, which makes it difficult to process it in processes such as molding and stretching, which will be described later. In addition, the solvent used is halogen-based organic solvent such as methylene chloride. However, if halogenated solvents remain in the resin, it is not recommended to use this resin. If the molded article is incorporated into electronic devices, it may cause corrosion of the metal parts. The resin obtained by this process does not contain solvents, which is also useful for stabilizing the processing process and product quality. It is beneficial.
[0070] When polycarbonate resin is produced by melt polymerization, the monomer having the above-mentioned structural unit is The monomer, the carbonic acid diester, and the polymerization catalyst are mixed and transesterified (or polymerized) in the melt. This is also called a condensation reaction. The reaction rate is increased while removing the eliminated components from the system. At the end of the reaction, the reaction is carried out under high temperature and high vacuum conditions until the desired molecular weight is reached. The molten resin is discharged from the reactor to obtain the polycarbonate resin of the present invention.
[0071] The polycondensation reaction is carried out by adjusting the molar ratio of all dihydroxy compounds and all diester compounds used in the reaction. By carefully adjusting the reaction rate, it is possible to control the molecular weight of the resulting resin. In the case of the dihydroxy compound, the molar ratio of the diester carbonate to the total dihydroxy compound is 0.90 to 1.00. It is preferable to adjust the ratio to 1.10, and more preferably to adjust the ratio to 0.96 to 1.05. It is particularly preferable to adjust it to 0.98 to 1.03.
[0072] If the molar ratio is too far above or below the range, it will be impossible to produce a resin with the desired molecular weight. If the molar ratio is too small, the number of hydroxyl groups in the produced resin increases. In addition, the unreacted dihydroxy compound may cause deterioration of the thermal stability of the resin. It remains in the oil in large quantities and causes dirt on the molding machine and poor appearance of the molded product in the subsequent molding process. On the other hand, if the molar ratio is too large, the transesterification reaction may not proceed smoothly under the same conditions. The rate of reaction is decreased, and the amount of residual carbonic acid diester in the produced resin increases. Molecular components can also lead to problems during fabrication.
[0073] The melt polymerization method is usually carried out in two or more stages. The reaction may be carried out in two or more steps by sequentially changing the conditions in a reactor, or in two or more steps. It is possible to carry out the process in two or more steps by changing the conditions for each step using a vessel, but this is not recommended due to the production efficiency. From the viewpoint of the polymerization, two or more reactors, preferably three or more reactors, are used. The process may be batch, continuous, or a combination of batch and continuous, but the production efficiency is important. From the viewpoint of rate and quality stability, the continuous type is preferred.
[0074] In polycondensation reactions, it is important to properly control the balance of temperature and pressure in the reaction system. If either the temperature or pressure is changed too quickly, the unreacted monomers will react. As a result, dihydroxy compounds and carbonic acid diesters may be formed. In some cases, the molar ratio of the mixture may change, and a resin having the desired molecular weight may not be obtained. The polymerization rate of the polycondensation reaction depends on the balance between the hydroxyl group terminal and the carbonate group terminal. Therefore, especially in continuous polymerization, the residual amount of unreacted monomer is controlled by the If the balance of terminal groups changes due to polymerization, it becomes difficult to control the polymerization rate. However, there is a risk that the molecular weight of the resulting resin will vary greatly. The molecular weight of the resin is related to the melt viscosity. Therefore, when the resin is molded, the melt viscosity fluctuates, and it is difficult to produce molded products of uniform dimensions. This may lead to problems such as not being able to obtain sufficient information.
[0075] Furthermore, if unreacted monomers are distilled off, not only the balance of the terminal groups but also the copolymerization composition of the resin will be affected. The composition of the polyimide of the present invention may deviate from the desired composition, and the mechanical properties and optical properties may be affected. In the case of a retardation film made from a carbonate resin, the wavelength dispersion of the retardation is determined by the full wavelength dispersion in the resin. The ratio of the olefin monomer to the other copolymerization components is controlled, so the ratio during polymerization If this is lost, it may become difficult to obtain the desired characteristics.
[0076] Hereinafter, the melt polycondensation reaction process will be described as a step of consuming monomers to produce oligomers ( The first step is to polymerize the polymer to the desired molecular weight (the second step). This will be described in two parts: the first reaction and the second reaction. Specifically, the following reaction conditions can be adopted for the first stage reaction: That is, the internal temperature of the polymerization reactor is usually 130° C. or higher, preferably 150° C. or higher, and more preferably Preferably, the temperature is 170° C. or higher and usually 250° C. or lower, more preferably 240° C. or lower, and even more preferably The temperature is set to a range of 230°C or less. In addition, the pressure of the polymerization reactor (hereinafter, pressure is absolute pressure) ) is usually 70 kPa or less, preferably 50 kPa or less, more preferably 30 kPa or less. Pa or less, and usually 1 kPa or more, preferably 3 kPa or more, more preferably 5 kPa or more The reaction time is set within the above range. The reaction time is usually 0.1 hours or more, preferably 0.5 hours. and usually 10 hours or less, preferably 5 hours or less, more preferably 3 hours or less. Set within the range.
[0077] In the first step, the monohydroxy compound derived from the diester compound is removed from the reaction system. For example, diphenyl carbonate is used as the carbonic acid diester. In the case where the reaction is carried out in the first stage, the monohydroxy compound distilled out of the reaction system is It is an ol. In the first stage reaction, the lower the reaction pressure, the more the polymerization reaction can be promoted. However, on the other hand, the amount of unreacted monomer distilled off is large. In order to achieve both the promotion of the reaction by reducing the pressure, a reactor equipped with a reflux condenser should be used. It is particularly effective to use a reflux condenser in the early stages of the reaction when there is a large amount of unreacted monomer.
[0078] The second stage reaction continues as the pressure in the reaction system is gradually reduced from the pressure in the first stage. While removing monohydroxy compounds from the reaction system, the pressure in the reaction system is finally reduced to 5 kPa or less. The internal temperature is usually set to 2 kPa or less, preferably 3 kPa or less, more preferably 1 kPa or less. 10°C or higher, preferably 220°C or higher, and usually 260°C or lower, preferably 255°C or lower The reaction time is usually set within the range below. The reaction time is usually 0.1 hours or more, preferably 0.5 hours or more. More preferably, the reaction time is 1 hour or more, and usually 10 hours or less, preferably 5 hours or less, more preferably 1 hour or more. The time is preferably set to 3 hours or less. This suppresses side reactions such as coloring, thermal deterioration, and crosslinking, and reduces the color. To obtain a resin with good phase, weather resistance, and thermal stability, the maximum internal temperature in all reaction steps should be within 2 The temperature is preferably 60° C. or less, more preferably 255° C. or less, and even more preferably 250° C. or less. In the present invention, the dihydroxy compound serving as the raw material for the structural unit (A) is polymerized at an excessively high temperature. There is a concern that the reaction will cause decomposition, resulting in branched components, and the resulting polymer will crosslink and gel. If gel is generated, the mechanical properties of the resulting resin may be deteriorated.
[0079] A transesterification catalyst that can be used in polymerization (hereinafter simply referred to as a "catalyst" or a "polymerization catalyst") ) has a very large effect on the reaction speed and the color and thermal stability of the resin obtained by polycondensation. The catalyst can have a significant effect on the transparency, color, heat resistance, and thermal stability of the produced resin. As long as it satisfies the requirements for the above and mechanical strength, the long-form periodic table Group 1 or 2 metal compounds (hereinafter simply referred to as "Group 1" and "Group 2"), basic boron Basicization of basic phosphorus compounds, basic ammonium compounds, amine compounds, etc. Preferred are compounds selected from the group consisting of metals in Group 2 of the long periodic table and lithium. At least one metal compound selected from the following is used.
[0080] As the Group 1 metal compound, for example, the following compounds can be used. It is also possible to employ Group 1 metal compounds other than those mentioned above. Sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium bicarbonate Sodium, potassium bicarbonate, lithium bicarbonate, cesium bicarbonate, sodium carbonate, carbon potassium carbonate, lithium carbonate, cesium carbonate, sodium acetate, potassium acetate, lithium acetate , Cesium acetate, Sodium stearate, Potassium stearate, Lithium stearate , Cesium stearate, Sodium borohydride, Potassium borohydride, Hydrogenated Lithium boron, cesium borohydride, sodium tetraphenylborate, tetraphenylborate Potassium tetraphenylborate, lithium tetraphenylborate, cesium tetraphenylborate, Sodium benzoate, potassium benzoate, lithium benzoate, cesium benzoate, phosphoric acid Disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, dicesium hydrogen phosphate phenyl phosphate, disodium phenyl phosphate, dipotassium phenyl phosphate, dilithium phenyl phosphate Alcohols of sodium, potassium, lithium, and cesium, diphenylphosphate ester, phenolate, disodium, dipotassium, and dilithium salts of bisphenol A Of these, lithium salts are preferred from the viewpoint of polymerization activity and the color of the resulting resin. It is preferable to use a mixture of these.
[0081] As the Group 2 metal compound, for example, the following compounds can be used. It is also possible to employ Group 2 metal compounds other than those mentioned above. Calcium hydroxide, barium hydroxide, magnesium hydroxide, strontium hydroxide, carbon Calcium bicarbonate, barium bicarbonate, magnesium bicarbonate, strontium bicarbonate , calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, calcium acetate , barium acetate, magnesium acetate, strontium acetate, calcium stearate , barium stearate, magnesium stearate, strontium stearate.
[0082] Among these, magnesium compounds, calcium compounds, and barium compounds are used. From the viewpoints of polymerization activity and color of the resulting resin, a magnesium compound and / or It is more preferable to use a calcium compound, and it is most preferable to use a calcium compound. I wish. In addition, a basic boron compound may be used in combination with the Group 1 metal compound and / or the Group 2 metal compound. Basic compounds such as basic phosphorus compounds, basic ammonium compounds, and amine compounds It is also possible to use a combination of a long-form group 2 metal and lithium. It is particularly preferable to use at least one metal compound selected from the group:
[0083] The amount of the polymerization catalyst used is usually determined based on the total amount of dihydroxy compounds used in the polymerization in terms of the amount of metal. 0.1 μmol to 300 μmol, preferably 0.5 μmol to 100 μmol per mol mol. If the amount of catalyst is too small, the polymerization rate will be slow, so Therefore, the thermal history during the polymerization reaction increases. The color and weather resistance of the resulting resin may be deteriorated. During the polymerization, the dihydroxy compound and the carbonic acid diester compound are volatilized, and the molar ratio of the dihydroxy compound and the carbonic acid diester compound is lost. On the other hand, if the amount of the polymerization catalyst used is too large, the desired molecular weight may not be achieved. This can lead to unwanted side reactions, which can cause deterioration in the color of the resulting resin and discoloration or decomposition of the resin during molding. It's possible.
[0084] Among the group 1 metals, sodium, potassium, and cesium tend to cause color changes when contained in large amounts in resin. These metals are not only introduced into the catalyst used, but also into the These metals in resins, regardless of their origin, can be present in a wide range of materials and can be introduced into the reactor. The total amount of the compounds is, in terms of metal amount, 2 μm per 1 mol of the total dihydroxy compounds. ol or less, preferably 1 μmol or less, and more preferably 0.5 μmol or less. .
[0085] The polycarbonate resin of the present invention is usually cooled and solidified after polymerization as described above. It can be pelletized using a rotary cutter, etc. The pelletization method is not limited. However, the polycarbonate resin is extracted in a molten state from the final polymerization reactor and then The final stage of the polymerization reactor is cooled and solidified in the form of a pellet, and the molten Polycarbonate resin is fed into a single-screw or twin-screw extruder, melt-extruded, and then cooled and solidified. The polycarbonate is then pelletized in a molten state from the final polymerization reactor. The resin is extracted, cooled and solidified in the form of strands, pelletized, and then reassembled. Polycarbonate resin is fed into a single-screw or twin-screw extruder, melt-extruded, and then cooled and solidified. and pelletizing the mixture.
[0086] The second aspect of the present invention is a method for producing a dihydroxy compound having two or more reactive functional groups, the method comprising the steps of: Rupo The present invention relates to a method for producing a polycarbonate resin, comprising the steps of: mixing a triorganosiloxane to obtain a raw material solution; and carrying out a polycondensation reaction of the raw material solution, a carbonic acid diester, and a polymerization catalyst in a reactor.
[0087] [ka]
[0088] In the formula (3), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkyl group having 6 to 20 carbon atoms. Xylene group; R 1 ~R 2 has a branched or linear alkyl group having 1 to 20 carbon atoms, or a substituent a cycloalkyl group having 6 to 20 carbon atoms; m is an integer of 0 to 10) In the above formula (3), W and R 1 , R 2 The details of m are the same as those in the above formula (1). Same here.
[0089] In the method of the present invention, a dihydroxy compound including the dihydroxy compound represented by the above formula (3) is The compound is particularly preferably a spiro glycol represented by the following formula (X): In this case, it has excellent compatibility with polyorganosiloxanes having two or more reactive functional groups. Therefore, it is possible to produce a copolymer polycarbonate resin with excellent chemical resistance.
[0090] [ka]
[0091] The polyorganosiloxane having two or more reactive functional groups used in the method of the present invention is In order to introduce the structural unit (B) contained in the copolymeric polycarbonate resin of the first embodiment of the present invention, For this purpose, it is possible to use a polyorganosiloxane having two or more reactive functional groups. can. As described above, the method for producing a polycarbonate resin according to the second aspect of the present invention comprises reacting a carboxylic acid ester represented by the above formula (3) and a dihydroxy compound having two or more reactive functional groups, A process for obtaining a raw material solution (hereinafter referred to as a raw material dissolving process) by mixing the polyorganosiloxane to be used. ) may be available.
[0092] Raw material melting process In the method of the present invention, a dihydroxy compound including a dihydroxy compound represented by the above formula (3) and a compound having two or more reactive functional groups are mixed. Rupo The method of mixing the triorganosiloxane to obtain the raw material solution is not particularly limited. For example, the dihydroxy compound represented by the above formula (3) is melted in advance, and a liquid triorganosiloxane having two or more reactive functional groups is added to a raw material dissolving tank having the melt. Rupo A method of dissolving a triorganosiloxane in water, or a method of dissolving a dihydroxy compound represented by the above formula (3) in water, which has two or more reactive functional groups in the liquid, Rupo A method in which triorganosiloxane is simultaneously dissolved can be preferably used.
[0093] The temperature at which the raw material solution is prepared is not particularly limited, but is preferably 160° C. or less, and more preferably 15 More preferably, the temperature is 0° C. or lower. On the other hand, the temperature is preferably 80° C. or higher, and more preferably 90° C. or higher. By setting the internal temperature of the dissolution tank within the above range, the dihydroxy compound represented by the above formula (3) can be dissolved. It can suppress the decomposition reaction and coloring of dihydroxy compounds, including those containing hydroxyl groups, and also prevents crystallization during transportation. This also avoids the risk of blocking pipes, etc.
[0094] A raw material dissolving tank can be used to prepare the raw material solution. The raw material dissolving tank may be a single tank, but two or more tanks may be connected in series. The dihydroxy compound (A) supplied to the disintegrator is usually at room temperature. Therefore, the temperature required for dissolution is higher than the temperature required to maintain the liquid state. In the case of , the part that has already been melted continues to be exposed to high temperatures, making it more susceptible to thermal degradation. By transferring the liquid dissolved in the first layer to the second tank, the second layer is maintained at a lower temperature than the first tank. It is possible. The method for producing a polycarbonate resin according to the second aspect of the present invention includes the steps (hereinafter, This may be referred to as a polymerization reaction process.
[0095] Polymerization reaction process In the method of the present invention, the raw material solution, a carbonic acid diester, and a polymerization catalyst are added to a reactor. The method of polycondensation reaction in the first aspect of the present invention is not particularly limited. The above-mentioned melt polycondensation reaction method is preferably used as a method for producing the synthetic polycarbonate resin. It is possible.
[0096] A dihydroxy compound including the dihydroxy compound represented by the above formula (3) and a reactive functional Polyorganosiloxanes having two or more groups have high compatibility with polyorganosiloxanes. Therefore, the raw material solution used as the reaction solution in the polymerization reaction becomes homogeneous. In the present invention, the reaction of polyorganosiloxane alone is reduced, and the polyorganosiloxane in the polymer is The dispersion of the structural unit domains derived from the alkane is improved and at the same time the domains become smaller. As a result, the resulting polymer exhibits high chemical resistance and, in some embodiments, improved transparency. It is thought that.
[0097] (Molded product (molded product)) The copolymeric polycarbonate of the present invention can be produced by conventional molding methods such as injection molding, extrusion molding, and compression molding. It can be made into a molded article by the method described in the present application. Furthermore, the copolymeric polycarbonate of the present invention may be optionally treated with an acid prior to various molding processes. Antioxidants, heat stabilizers, light stabilizers, neutralizing agents, UV absorbers, release agents, colorants, antistatic agents, Additives such as lubricants, lubricants, plasticizers, compatibilizers, flame retardants, and fillers are added in tumblers, supermarkets, and other containers. Mixer, floater, V-type blender, Nauta mixer, Banbury mixer, extrusion The mixture can also be mixed using a mixer or the like.
[0098] (Heat stabilizer) The polycarbonate resin of the present invention may be modified, if necessary, to lower the molecular weight during melt processing or the like. In order to prevent deterioration of the color tone and color shift, a heat stabilizer can be added. Examples of the heat stabilizer include commonly known hindered phenol-based heat stabilizers and / or phosphorus-based heat stabilizers. can be done.
[0099] As the hindered phenol compound, for example, the following compounds can be used: do. 2,6-di-tert-butylphenol, 2,4-di-tert-butylphenol , 2-tert-butyl-4-methoxyphenol, 2-tert-butyl-4,6-di Methylphenol, 2,6-di-tert-butyl-4-methylphenol, 2,6-di -tert-Butyl-4-ethylphenol, 2,5-di-tert-butylhydroquinone n-Octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) phenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5' -Methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,2'- Methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-Methylene Bis-(6-cyclohexyl-4-methylphenol), 2,2'-ethylidene- bis-(2,4-di-tert-butylphenol), tetrakis-[methylene-3-( ',5'-Di-tert-butyl-4'-hydroxyphenyl)propionate]-Meth 1,3,5-trimethyl-2,4,6-tris-(3,5-di-tert-butyl- 4-hydroxybenzyl)benzene, etc. Among them, tetrakis-[methylene-3-(3', 5'-di-tert-butyl-4'-hydroxyphenyl)propionate]-methane, n-Octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl propionate, 1,3,5-trimethyl-2,4,6-tris-(3,5-di-t It is preferred to use ert-butyl-4-hydroxybenzyl)benzene.
[0100] Examples of phosphorus-based compounds include phosphorous acid, phosphoric acid, phosphonous acid, and phosphonic acid shown below. Phosphoric acid and their esters can be used, but phosphorus compounds other than these can also be used. It is also possible to employ a mixture. Triphenyl phosphite, tris(nonylphenyl) phosphite, tris(2,4 -Di-tert-butylphenyl) phosphite, tridecyl phosphite, trioctyl phenyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, Dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, mono Butyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite Phenyl phosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentane Taerythritol diphosphite, 2,2-methylenebis(4,6-di-tert-butyl) Bis(nonylphenyl)octylphosphite, Bis(nonylphenyl)pentaerythritol diphosphite Sulfite, Bis(2,4-di-tert-butylphenyl)pentaerythritol diphos Sphite, distearyl pentaerythritol diphosphite, tributyl phosphate phosphate, triethyl phosphate, trimethyl phosphate, triphenyl phosphate, di Phenyl mono-orthoxenyl phosphate, dibutyl phosphate, dioctyl phosphate phosphate, diisopropyl phosphate, 4,4'-biphenylenediphosphinic acid tetrakis (2,4-di-tert-butylphenyl), benzenephosphonic acid dimethyl, benzene phosphinic acid dimethyl Diethyl sulfonate, dipropyl benzenephosphonate.
[0101] These heat stabilizers may be used alone or in combination of two or more. Such a heat stabilizer may be added to the reaction liquid during melt polymerization, or may be added to the resin using an extruder. When the film is produced by the melt extrusion method, the heat stabilizer may be added to the extruder. Alternatively, the heat stabilizer or the like may be added to the resin in advance using an extruder to form a film. The powder may be in the form of pellets or the like.
[0102] The amount of these heat stabilizers to be added is 0.0001 parts by weight or more when the resin is 100 parts by weight. Preferably, the amount is 0.0005 parts by weight or more, more preferably 0.001 parts by weight or more, It is preferable that the amount is 1 part by weight or less, more preferably 0.5 parts by weight or less, and more preferably 0.2 parts by weight or less. Parts or less is even more preferred.
[0103] (Catalyst deactivator) In order to neutralize and deactivate the catalyst used in the polymerization reaction of the polycarbonate resin of the present invention, The addition of an acidic compound can improve color tone and thermal stability. The acidic compounds used in the present invention include compounds having a carboxylic acid group, a phosphoric acid group, or a sulfonic acid group. Compounds or esters thereof can be used, particularly compounds represented by the following formula (7) or (8): It is preferable to use a phosphorus-based compound containing a partial structure represented by the following formula:
[0104] [ka]
[0105] The phosphorus-based compound represented by the formula (7) or (8) includes phosphoric acid, phosphorous acid, phosphonic acid, Examples of the phosphoric acid include phosphoric acid, hypophosphorous acid, polyphosphoric acid, phosphonic acid esters, and acidic phosphate esters. Among the above, phosphorous acid and phosphonic acid have better effects on catalyst deactivation and color suppression. Among these, phosphorous acid and phosphonic acid esters are preferred, with phosphorous acid being particularly preferred. Phosphonic acids include phosphonic acid (phosphorous acid), methylphosphonic acid, and ethylphosphonic acid. , vinylphosphonic acid, decylphosphonic acid, phenylphosphonic acid, benzylphosphonic acid, Aminomethylphosphonic acid, methylenediphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid phosphonic acid, 4-methoxyphenylphosphonic acid, nitrilotris(methylenephosphonic acid), propylphosphonic anhydride and the like.
[0106] Phosphonate esters include dimethyl phosphonate, diethyl phosphonate, and phosphonic acid Bis(2-ethylhexyl), dilauryl phosphonate, dioleyl phosphonate, phosphonic acid diphenyl phosphonate, dibenzyl phosphonate, dimethyl methylphosphonate, dimethyl methylphosphonate Phenyl, diethyl ethylphosphonate, diethyl benzylphosphonate, phenylphosphonic acid Dimethyl phenylphosphonate, Diethyl phenylphosphonate, Dipropyl phenylphosphonate, (Methoxy Diethyl methylphosphonate, diethyl vinylphosphonate, hydroxymethylphosphonic acid Diethyl, (2-hydroxyethyl) dimethyl phosphonate, p-methylbenzyl phosphonate Diethyl phosphonoacetate, Diethyl phosphonoacetate, Ethyl diethyl phosphonoacetate, Diethyl phosphonoacetate tert-Butyl Phosphonate, (4-Chlorobenzyl)diethyl Phosphonate, Dicyanophosphonate Ethyl, diethyl cyanomethylphosphonate, 3,5-di-tert-butyl-4-hydro Diethyl oxybenzylphosphonate, diethyl phosphonoacetaldehyde diethyl acetate and diethyl (methylthiomethyl)phosphonate.
[0107] Acid phosphate esters include dimethyl phosphate, diethyl phosphate, divinyl phosphate, Dipropyl phosphate, dibutyl phosphate, bis(butoxyethyl) phosphate, bis(2-ethylhexyl) phosphate ethylhexyl), diisotridecyl phosphate, dioleyl phosphate, distearyl phosphate, Phosphate diesters such as diphenyl phosphate and dibenzyl phosphate, or diesters and monoesters ester mixture, diethyl chlorophosphate, zinc stearyl phosphate, and the like.
[0108] These may be used alone or in any combination and ratio of two or more. It may be used. If the amount of the phosphorus compound added to the resin is too small, the effect of preventing catalyst deactivation and coloring is insufficient. If the amount is too high, the resin may become discolored, and durability tests may be adversely affected, especially under high temperature and humidity conditions. In the experiment, the resin was easily colored. Add an amount corresponding to the amount of catalyst. The phosphorus compound preferably contains 0.5 to 5 times the molar amount of phosphorus atoms. The amount is preferably 0.7 times or more and 4 times or less, and more preferably 0.8 times or more and 3 times or less. l or less is preferred.
[0109] (Polymer alloy) In addition, the copolymer polycarbonate of the present invention has the following properties: For the purpose of adjustment, resins other than the copolymer polycarbonate of the present invention (hereinafter simply referred to as "other resins") It is also possible to add fats such as glyceryl stearate, ... and glyceryl stearate. Other resins include, for example, polyethylene terephthalate resin and polytrimethylene Thermoplastic polyester resins such as polybutylene terephthalate and polybutylene terephthalate resins; Styrene resin, high impact polystyrene resin (HIPS), acrylonitrile-styrene copolymer Polymer (AS resin), acrylonitrile-styrene-acrylic rubber copolymer (ASA resin) , acrylonitrile-ethylene propylene rubber-styrene copolymer (AES resin), etc. Styrene resins; polyolefin resins such as polyethylene resins and polypropylene resins; poly Amide resin; Polyimide resin; Polyetherimide resin; Polyurethane resin; Polyphenylene Polyphenylene ether resin; Polyphenylene sulfide resin; Polysulfone resin; Polymethacrylate rate resins, etc.
[0110] The other resins may be contained alone or in any combination of two or more. The content may be in a ratio. The molded articles obtained by molding the copolymeric polycarbonate of the present invention are particularly excellent in weather resistance, chemical resistance, etc. Due to its excellent properties, it is used in automobile interior and exterior parts, electrical equipment parts, electronic and electrical materials, outdoor building parts, and cosmetic containers. It can be used in a wide range of fields, such as for equipment. EXAMPLES
[0111] Examples of polycarbonate copolymers are shown below, but the present invention is not limited to the above without departing from the gist of the invention. The following examples are not intended to limit the scope of the present invention. The methods for measuring each characteristic are as follows: It is.
[0112] (1) Glass transition temperature The glass transition temperature of the resin was measured using a differential scanning calorimeter (DSC) manufactured by SII NanoTechnology Co., Ltd. The measurement was performed using a 6220. Approximately 10 mg of the resin sample was placed in an aluminum pan manufactured by the same company and sealed. The temperature was increased from 30°C to 200°C at a rate of 20°C / min under a nitrogen flow of 50 mL / min. After holding the temperature for 10 minutes, the sample was cooled to 30° C. at a rate of 20° C. / min. The sample was held at 30° C. for 3 minutes, The temperature was then increased again to 200°C at a rate of 20°C / min. The line extending from the low-temperature baseline to the high-temperature side and the curve in the step-like change part of the glass transition are The extrapolated glass transition onset is the temperature at which the line intersects with the tangent drawn at the point where the slope of the line is maximum. The temperature was determined and was taken as the glass transition temperature.
[0113] (2) Weather resistance test The pellets of the polycarbonate resin composition were subjected to a pressure reduction of 200 Pa or less until the glass transition temperature Dry the pellets at -10°C for 12 hours or more. Then, put about 4g of the dried pellets into a small heat press. Using a machine (As One Corporation, AH-2003C AH-1TC), the length was 7 cm, width was 7 cm, A spacer with a thickness of 0.5 mm was used, and polyimide films were placed above and below the sample. Preheat at 00 to 230°C for 3 minutes, pressurize at 7MPa for 5 minutes, and then remove with the spacer. Then, the mixture was cooled to prepare a sheet product.
[0114] The obtained sheet molded product was used for the Aisan Cube Xenon SCX4 manufactured by Iwasaki Electric Co., Ltd. The sheet was treated for 100 hours at an irradiation intensity of 60 W / m2 using 1000. The color tone was measured using a Konica Minolta CM-5 spectrophotometer in accordance with ASTM D1925. The plate was placed in the measurement chamber and the YI (Yellowness Index) value of the transmitted light was measured. The smaller the difference between the YI after irradiation and the YI before treatment (ΔYI), the greater the effect of UV irradiation. This indicates that there is little discoloration and excellent weather resistance. <Evaluation> When ΔYI is less than 1.0: If ΔYI is 1.0 or more: ×
[0115] (3) Transparency The sheet molded product obtained in (2) above before the weather resistance test was visually inspected in the thickness and width directions. The samples were checked and rated as ◯ for those with the same level of transparency as Comparative Example 1, and rated as ◯ for those with inferior transparency to Comparative Example 1. Those that were cloudy were marked as x.
[0116] (4) Measurement of total light transmittance The sheet molded product obtained in (2) above before the weather resistance test was used to measure the color and turbidity simultaneously (Japan The measurement was performed in accordance with JIS K7105 using a meter (Denshoku Kogyo Co., Ltd., Model: COH-400). It was determined.
[0117] (5) Measurement of water absorption rate The pellets of the polycarbonate resin composition were subjected to a pressure reduction of 200 Pa or less until the glass transition temperature Dry the pellets at -10°C for 12 hours or more. Then, put about 4g of the dried pellets into a small heat press. Using a machine (As One Corporation, AH-2003C AH-1TC), the length was 14 cm, the width was 14 cm A spacer with a thickness of 0.1 mm was used, and polyimide films were placed on the top and bottom of the sample. Preheat at 200-230℃ for 3 minutes, pressurize at 7MPa for 5 minutes, and then remove the spacer. The mixture was then cooled to prepare a sheet.
[0118] The obtained film was cut into a square sample measuring 100 mm in length and 100 mm in width. The sample was dried for 24 hours or more at a temperature of glass transition temperature -10℃ under a reduced pressure of 200 Pa or less. The weight of the dried sample was measured to the nearest 0.1 mg, and this value was taken as the dry weight. The dried samples were immersed in desalted water at 23°C for 72 hours or more. After removing the sample, wipe off all the moisture on the surface with a clean, dry cloth or filter paper, and then place the sample in a 0 The weight of absorbed water was measured within 1 minute after removing it from the water. The water absorption rate was calculated using Equation 1. (Water absorption weight - Dry weight) / Dry weight x 100 = Water absorption rate (%)...Formula 1
[0119] (6) Chemical resistance test The pellets of the polycarbonate resin composition were subjected to a pressure reduction of 200 Pa or less until the glass transition temperature Dry the pellets at -20°C for 12 hours or more. Then, put about 4g of the dried pellets into a small heat press. Using a machine (As One Corporation, AH-2003C AH-1TC), the length was 14 cm and the width was 2 cm. A spacer with a thickness of 1 mm was used, and polyimide films were placed above and below the sample. Preheat at 0 to 230°C for 3 minutes, pressurize at 7MPa for 5 minutes, then remove with the spacer. The sheet was cooled and cut into a rectangle measuring 10 cm in length and 2 cm in width. Test pieces were prepared as follows.
[0120] A surfactant, IGEPAL CA630 (MP Bioja Co., Ltd.), was applied to the surface of the test piece. The plate is then attached to the 1 / 4 elliptical jig shown in Figure 1, with a major axis of 100 mm and a minor axis of 40 mm. The test piece was left in an environment of 25℃ × 60% RH for 72 hours, and the thickness of the test piece that reached from the front to the back was measured. The position X where the crack occurs was measured, and the critical strain value was calculated using Equation 1. Based on this, the chemical resistance was evaluated as follows. ε: Critical strain (%) a: Long axis of the jig (=120mm) b: Short axis of the jig (=40 mm) t: thickness of test piece (=1.0mm) X: Distance from crack location (mm)
[0121] <Evaluation> If the critical strain value (ε) is 0.7% or more: Yes If the critical strain value (ε) is less than 0.7%, the result is ×
[0122]
number
[0123] (7) Average repeat number of dimethylsiloxane units, n 1 The average repeat number n of dimethylsiloxane units was calculated by H-NMR measurement. The apparatus and conditions used are as follows: Equipment: JNM-ECZ400S (manufactured by JEOL Ltd.) ·Measurement temperature: 30℃ Relaxation time: 6 seconds ·Number of times of accumulation: 64 times ·Sample amount: 5 to 15 mg Solvent: deuterated chloroform As an example of the polyorganosiloxane used in the Examples and Comparative Examples described below, dimethylsiloxane Explain how to calculate the average repeat number of units, n.
[0124] <In the case of polydimethylsiloxane represented by the following formula (V-1)> Range for calculating integral value (a): 0.04 to 0.1 ppm: derived from the methyl group of the dimethylsiloxane part (number of protons: 6) (b): 0.5 to 0.6 ppm: protons derived from methylene groups in the carbinol-modified portions at both ends Number: 4) {(a) / ((b) / 4)) / 6}-1 = average repeat number of dimethylsiloxane units n
[0125] <In the case of polydimethylsiloxane represented by the following formula (V-2)> Range for calculating integral value (a): 0.04 to 0.1 ppm: derived from the methyl group of the dimethylsiloxane part (number of protons: 6) (b): 3.8 to 3.9 ppm: methyl groups from the eugenol-modified portions at both ends (proton number :6) {(a) / ((b) / 6)) / 6}-1 = average repeat number of dimethylsiloxane units n
[0126] <In the case of polydimethylsiloxane represented by the following formula (V-3)> (a): 0.04 to 0.1 ppm: derived from the methyl group of the dimethylsiloxane part (number of protons: 6) (b): 0.5 to 0.6 ppm: methylene groups in terminal carbinol-modified portions and terminal butylene portions Origin (proton count: 4) {(a) / ((b) / 4)) / 6}-1 = average repeat number of dimethylsiloxane units n
[0127] [ka]
[0128] [Compound abbreviation] The abbreviations for the compounds used in the following Synthesis Examples, Examples and Comparative Examples are as follows. ISB: Isosorbide (manufactured by Rocket Fleuret, product name: POLYSORB) SPG: Spiroglycol (manufactured by Mitsubishi Gas Chemical Co., Ltd.) CHDM: 1,4-cyclohexanedimethanol (cis, trans mixture, SK Chemical (Manufactured by Lexel) 1,6-HD: 1,6-Hexanediol (BASF) DPC: Diphenyl carbonate (Mitsubishi Chemical) PCD: Benebiol (Mitsubishi Chemical, grade name: HS0840H) Polyorganosiloxane-1: X-22-160AS, both terminal groups represented by the formula (V-1) Rubinol modified dimethylsiloxane, number average molecular weight: 970, dimethylsiloxane unit Average repeat number n: 10 (Shin-Etsu Chemical Co., Ltd.) Polyorganosiloxane-2: BY16-201, a polyorganosiloxane having both terminal carboxylates represented by the formula (V-1) Nol-modified dimethylsiloxane Number average molecular weight: 1860, Average repeating number of dimethylsiloxane units: Number of repetitions: 22 (Dow Corning Toray Co., Ltd.) Polyorganosiloxane-3: EXL1414T (Sabic)-containing polyorgano Siloxane, polydimethylsiloxane modified with eugenol at both ends represented by formula (V-2), Average molecular weight: 3900, average repeat number of dimethylsiloxane units: 48 Polyorganosiloxane-4: FM-0411, number average molecular weight: 1140, formula (V-3) The average of the dimethylsiloxane units, which is a one-terminal carbinol-modified dimethylsiloxane represented by Number of repetitions: 13 (JNC) Polyorganosiloxane-5: XP1459, a carbinolate at both ends represented by the formula (V-1) Modified dimethylsiloxane, number average molecular weight 600, average repeating number of dimethylsiloxane units Number of pieces: 5 (JNC)
[0129] [Example 1] ISB 8.49g (0.058mol), SPG 73.70g (0.242mol) ), Polyorganosiloxane-1 9.74g (0.010mol), DPC 66.4 7g (0.310mol) and 1.09×10 calcium acetate monohydrate as a catalyst - 2 g (6.21 × 10 -5 mol) was charged into a reactor, and the inside of the reactor was purged with nitrogen under reduced pressure. The raw materials were dissolved in a reactor at 150°C for 30 minutes under a nitrogen atmosphere while stirring. Reaction 1 In the second step, the temperature was raised to 220°C over 30 minutes, and the reaction was carried out at normal pressure for 30 minutes. The pressure was reduced from normal pressure to 13.3 kPa over 90 minutes, and the pressure was kept at 13.3 kPa for 30 minutes. The phenol generated by the reaction was extracted from the reaction system. The temperature was raised to 240°C over 15 minutes, while the pressure was reduced to 133 Pa or less over 20 minutes. The pressure was increased and the phenol generated was extracted from the reaction system. The pressure was restored, and the contents were extracted in the form of strands and pelletized with a rotary cutter. The above-mentioned various evaluations were carried out using the polycarbonate resin pellets. The evaluation results are shown below. Shown in 1.
[0130] [Example 2] ISB 16.98g (0.116mol), SPG 64.49g (0.212mol) l), Polyorganosiloxane-1 9.74g (0.010mol), DPC 73. 15g (0.341mol) and 1.49×10 calcium acetate monohydrate as a catalyst -2 g(8.45×10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol) of dimethylformamide was used. Polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used. The above-mentioned various evaluations were carried out, and the evaluation results are shown in Table 1.
[0131] [Example 3] ISB 8.49g (0.058mol), SPG 78.31g (0.257mol) ), Polyorganosiloxane-1 4.87g (0.005mol), DPC 68.6 4g (0.320mol) and 1.41×10 calcium acetate monohydrate as a catalyst - 2 g (8.01 × 10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol of Polycarbonate resin pellets were obtained. The various evaluations described above were carried out, and the evaluation results are shown in Table 1.
[0132] [Example 4] ISB 12.74g (0.087mol), SPG 73.70g (0.242mol) l), Polyorganosiloxane-1 4.87g (0.005mol), DPC 71. 62g (0.334mol) and 1.47×10 calcium acetate monohydrate as a catalyst -2 g(8.36×10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol) of dimethylformamide was used. Polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used. The above-mentioned various evaluations were carried out, and the evaluation results are shown in Table 1.
[0133] [Example 5] CHDM 16.95g (0.118mol), SPG 64.49g (0.212m ol), Polyorganosiloxane-1 9.74g (0.010mol), DPC 72 .71g (0.339mol), and 1.50x1 calcium acetate monohydrate as catalyst 0 -2 g(8.49×10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol of ethyl acetate was used. The polycarbonate resin pellets were obtained. The above-mentioned various evaluations were carried out using the same. The evaluation results are shown in Table 1.
[0134] [Example 6] 1,6-HD 16.39g (0.139mol), SPG 64.50g (0.21 2 mol), Polyorganosiloxane-1 9.73 g (0.010 mol), DPC 72.80g (0.363mol) and 1.27g calcium acetate monohydrate as catalyst ×10 -2 g (7.21 × 10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol of dimethylformamide was used. The polycarbonate resin pellets were obtained. The above-mentioned various evaluations were carried out using the test pieces. The evaluation results are shown in Table 1.
[0135] [Example 7] ISB 9.41g(0.064mol)1,6-HD 11.41g(0.097m ol), SPG 59.89g (0.197mol), Polyorganosiloxane-1 9 .74g (0.010mol), DPC 78.77g (0.368mol), and catalyst Calcium acetate monohydrate 0.97 x 10 -2 g(5.52×10 -5 mol) A polymerization reaction was carried out in the same manner as in Example 1, except that polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used to carry out the various evaluations described above. The results are shown in Table 1.
[0136] [Example 8] PCD 24.09g (0.035mol), SPG 59.88g (0.197mol) l), Polyorganosiloxane-1 9.74g (0.010mol), DPC 51. 82g (0.242mol) and 1.07×10 calcium acetate monohydrate as a catalyst -2 g (6.05 × 10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol) of dimethylformamide was used. Polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used. The above-mentioned various evaluations were carried out, and the evaluation results are shown in Table 1.
[0137] [Example 9] ISB 12.74g (0.087mol), SPG 73.71g (0.242mol) l), Polyorganosiloxane-2 4.93g (0.002mol), DPC 71. 43g (0.333mol) and 1.46×10 calcium acetate monohydrate as a catalyst -2 g(8.29×10 -5The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol) of dimethylformamide was used. Polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used. The above-mentioned various evaluations were carried out, and the evaluation results are shown in Table 1.
[0138] [Example 10] ISB 16.98g (0.116mol), SPG 64.49g (0.212mol) l), Polyorganosiloxane-2 9.87g (0.005mol), DPC 71. 70g (0.335mol) and 1.47×10 calcium acetate monohydrate as a catalyst -2 g (8.33 × 10 -5 The polymerization reaction was carried out in the same manner as in Example 1, except that 100 mol) of dimethylformamide was used. Polycarbonate resin pellets were obtained. The obtained polycarbonate resin pellets were used. The above-mentioned various evaluations were carried out, and the evaluation results are shown in Table 1.
[0139] [Comparative Example 1] ISB 16.98g (0.116mol), SPG 73.71g (0.242mol) l), 76.76 g (0.358 mol) of DPC, and calcium acetate monohydrate as a catalyst. Japanese 0.95×10 -2 g(5.37×10 -5 The same as in Example 1 except that 100 mol) was used. The polymerization reaction was carried out in the same manner as above to obtain polycarbonate resin pellets. The above-mentioned various evaluations were carried out using pellets of the resin. The evaluation results are shown in Table 1.
[0140] [Comparative Example 2] Using siloxane copolymer polycarbonate EXL1414T (manufactured by Sabic), The various evaluations described above were carried out, and the evaluation results are shown in Table 1. [Comparative Example 3] ISB 67.92g (0.465mol), FM-0411 0.48g (0.00 1 mol), DPC 99.56 g (0.465 mol), and calcium acetate as a catalyst. 6.55×10 -4 g (3.72 × 10 -6 mol) was used in the examples. The polymerization reaction was carried out in the same manner as in 1 to obtain polycarbonate resin pellets. The above-mentioned various evaluations were carried out using the carbonate resin pellets. The evaluation results are shown in Table 1.
[0141] [Comparative Example 4] ISB 63.23g (0.433mol), XP1459 5.30g (0.009m ol), 94.57g (0.441mol) of DPC, and 1g of calcium acetate as a catalyst. Hydrate 6.22×10 -4 g (3.53 × 10 -6 The same as in Example 1 except that 100 mol) was used. A polymerization reaction was carried out in the same manner to obtain polycarbonate resin pellets. The above-mentioned various evaluations were carried out using pellets of the resin. The evaluation results are shown in Table 1.
[0142] [Table 1]
[0143] [evaluation] As is apparent from Table 1, according to Examples 1 to 10 of the present invention, the structural unit (A) and the structural unit (B) are Polycarbonate resins having the structure (B) have excellent chemical resistance and weather resistance. Examples 1 to 8 are also excellent in transparency. Comparative Example 1, which does not contain the structural unit (B), and It can be seen that Comparative Examples 3 and 4, which do not contain the structural unit (A), have low chemical resistance. It is clear that Comparative Example 2, which does not contain the structural unit (B), is poor in both weather resistance and chemical resistance.
Claims
1. A copolymeric polycarbonate resin containing a structural unit (A) represented by the following formula (1) and a structural unit (B) derived from a polyorganosiloxane having two or more reactive functional groups: 【Chemistry 1】 (In formula (1), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms; R 1 ~R 2 represents a branched or linear alkyl group having 1 to 20 carbon atoms, or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent; m represents an integer of 0 to 10.
2. 2. The copolymeric polycarbonate resin according to claim 1, wherein, when the total weight of all structural units and linking groups constituting the resin is taken as 100% by weight, the content of the structural unit (A) is 40% by weight or more and 90% by weight or less, and the content of the structural unit (B) is 1.0% by weight or more and 20% by weight or less.
3. 3. The copolymeric polycarbonate resin according to claim 1, wherein the ratio of the contents of the structural unit (A) and the structural unit (B) is from 96 / 4 to 70 / 30.
4. The copolymeric polycarbonate resin according to any one of claims 1 to 3, wherein the reactive functional groups are each independently one or more selected from the group consisting of a hydroxyl group, a carboxyl group, an amine group, an alkenyl group, an ester group, a methacryloyl group, an acryloyl group, and a cyclic ether group.
5. 5. The copolymeric polycarbonate resin according to claim 1, wherein the structural unit (B) is represented by the following formula (2): 【Chemistry 2】 (In formula (2), n is 5 to 30. R 3 ~R 6 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. Each of X and X' independently represents an oxygen atom, or an organic residue having -C(=O)-, an ether structure, an amine structure, an aromatic structure, or an aliphatic structure. n represents the average number of repetitions of the polyorganosiloxane portion.
6. 6. The copolymeric polycarbonate resin according to any one of claims 1 to 5, comprising structural units (C) derived from one or more compounds selected from the group consisting of aliphatic dihydroxy compounds, alicyclic dihydroxy compounds, oxyalkylene glycols, and dihydroxy compounds having a heterocyclic structure in a total amount of 5 to 30% by weight, when the total weight of all structural units and linking groups constituting the resin is taken as 100% by weight.
7. 7. The copolymeric polycarbonate resin according to claim 1, wherein the polycarbonate resin has a water absorption rate of 1.1% or less.
8. 8. The copolymeric polycarbonate resin according to claim 1, wherein the copolymeric polycarbonate resin has a glass transition temperature of 50° C. or higher and 160° C. or lower.
9. A molded article comprising the copolymeric polycarbonate resin according to any one of claims 1 to 8.
10. A step of mixing a dihydroxy compound including a dihydroxy compound represented by the following formula (3) with a polyorganosiloxane having two or more reactive functional groups to obtain a raw material solution; The method for producing a copolymeric polycarbonate resin comprises a step of subjecting the raw material solution, a carbonic acid diester, and a polymerization catalyst to a polycondensation reaction. 【Chemistry 3】 (In formula (3), W is an alkylene group having 1 to 20 carbon atoms or a cycloalkylene group having 6 to 20 carbon atoms; R 1 ~R 2 represents a branched or linear alkyl group having 1 to 20 carbon atoms, or a cycloalkyl group having 6 to 20 carbon atoms which may have a substituent; m represents an integer of 0 to 10.
Citation Information
Patent Citations
JP1973064199A
Siloxane * carbonate composition
JP1980023183A
Copolycarbonate
JP2011241277A
Interior / exterior part of automobile
JP2013209585A
Multilayer body
JP2016007728A